2012
DOI: 10.3324/haematol.2012.066670
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological risk factors of acute chest syndrome and painful vaso-occlusive crisis in children with sickle cell disease

Abstract: BackgroundLittle is known about the effects of blood rheology on the occurrence of acute chest syndrome and painful vaso-occlusive crises in children with sickle cell anemia and hemoglobin SC disease. Design and MethodsTo address this issue, steady-state hemorheological profiles (blood viscosity, red blood cell deformability, aggregation properties) and hematologic parameters were assessed in 44 children with sickle cell anemia and 49 children with hemoglobin SC disease (8-16 years old) followed since birth. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 30 publications
7
111
1
1
Order By: Relevance
“…20,22,23,39 Therefore, SC and SS children were analyzed separately. Part of the results described here were previously included in a report on the initial SAPOTILLE cohort.…”
Section: Comparisons Between Ss and Sc Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…20,22,23,39 Therefore, SC and SS children were analyzed separately. Part of the results described here were previously included in a report on the initial SAPOTILLE cohort.…”
Section: Comparisons Between Ss and Sc Childrenmentioning
confidence: 99%
“…22 Serum lactate dehydrogenase and total bilirubin concentrations were determined by standard biochemical methods.…”
Section: Hematologic and Hemorheological Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It turns out that these factors have the opposite effect. Patients (both adults and children) who have decreased cell deformability and increased number of ISC and dense cells have mild disease with respect to the VOC [5][6][7]. A subsequent study showed patients whose RBC deformability averaged 37% or less of control values and whose dense cells averaged 22% of total circulating cells had fewer VOCs, less mortality, higher incidence of leg ulcers, and lower incidence of urinary tract infection although their Hb F was relatively low [8].…”
mentioning
confidence: 99%